Research on the Cognitive and mental Psychological Properties of Language Comprehension in the Process of Cultural Communication of athletes - Hong Zhang; Ping Liu; Hui Yang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The cognitive and mental psychological properties impact the communication channel between the process of cross-cultural communication between athletes. This article discusses the concept of sport psychology that is provisioned between athletes. Cognitive-behavioral Approach and Rational Emotional Behavior Therapy can predominate the Mental State of a sportsperson. This approach and therapy help the trainers to improve or generate positive sports psychology in athletes. REBT and CBA is based upon humanistic approach, as this approach helps the trainer to assist players with self-defeating behaviors and feelings. The article has collected data from sports athletes and data was processes on AMOS 26v and PLS.